Zambia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Selected Issues paper on Zambia reports that the authorities have outlined a range of alternative policy scenarios to achieve greater pro-poor growth. The thrust of these policies is to support higher growth in rural areas, where the incidence of poverty is particularly high, by investing more in infrastructure development, while also stepping up delivery of public services, notably in health and education. Implementing these alternative policies would require significantly more financial assistance from the donor community.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet